Avaliação das atitudes de design nos mecanismos de incubação - Aranha, Carlos Eduardo de Souza (Universidade do Vale do Rio dos Sinos, 2019)
This master's project aims to understand how the attitude of designers manifest themselves in the mechanisms of fostering innovation entrepreneurship, more specifically in incubators. Business incubators have long been regarded as one of the most important mechanisms for fostering innovative entrepreneurship and supporting startup development. However, many of the managers responsible for these incubation mechanisms are not prepared or comfortable to develop a work, increasingly complex due to the diversity of actors that orbit the innovation ecosystems, not only in our state, but worldwide. Therefore, this study seeks to address the aspects of the design attitude model proposed by Michlewski (2008, 2015) and to understand if these attitudes are present in the way incubator managers interact with the ecosystem in which they operate. The scope of the research is inserted in the innovation ecosystem of the state of Rio Grande do Sul, more specifically, in incubators of companies associated with REGINP - Rede Gaúcha de Ambientes de Inovação and CERNE 1.
Keywords: Design estratégico; Inovação e incubadoras de empresas; Design attitude; Strategic design, innovation and Incubators; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial